Prothrombin Complex Concentrate for Major Bleeding on Factor Xa Inhibitors: A Prospective Cohort Study - Schulman, Sam; Gross, Peter L.; Ritchie, Bruce; Nahirniak, Susan; Lin, Yulia; Lieberman, Lani; Carrier, Marc; Crowther, Mark A.; Ghosh, Indy; Lazo-Langner, Alejandro; Zondag, Michelle; On Behalf of the Study Investigators (Thrombosis and Haemostasis, 2018)
Oral factor Xa inhibitors are increasingly used for anticoagulation, but there is no approved reversal agent. Prothrombin complex concentrate (PCC) for the management of Xa-inhibitor–associated bleeding has been described in small case series and one cohort study. Patients on apixaban or rivaroxaban, suffering a major bleed, were treated at nine Canadian hospitals as per existing hospital protocol with a fixed dose of PCC 2,000 units and subsequently recruited for a 30-day follow-up. The treating physician evaluated the haemostatic effectiveness as observed during the first day as good, moderate or poor/none, using an assessment guide. Safety outcomes were thromboembolism or death. We recruited 66 patients with major bleeding who were treated with PCC and who were receiving rivaroxaban (56%) or apixaban (44%). The effectiveness was assessed as good in 65% (95% confidence interval [CI], 53–77), moderate in 20% (95% CI, 10–30) and poor/none in 15% (95% CI, 6–24). For the 36 patients with intracranial haemorrhage, the corresponding ratings were 67, 17 and 17%, and for 16 patients with gastrointestinal bleeding they were 69, 12 and 19%, respectively. There were nine deaths (14%) by 30 days, and five (8%) major thromboembolic events. In a post hoc analysis, according to International Society on Thrombosis and Haemostasis criteria, reversal was effective in 68% and ineffective in 32%. For major bleeding associated with oral Xa inhibitors, PCC may have a beneficial effect. The risk of thromboembolism after reversal of anticoagulation in patients with a prothrombotic background has to be taken into account.
Keywords: antagonists and inhibitors; haemorrhage; atrial fibrillation; rivaroxaban; apixaban